Approach to psychotherapy in generalized anxiety disorder in the primary health care - Aloufi, Khalid Kulaib; Kaki, Fatima Mohammad; Al Lashit, Abbas Hassan; Al Habshi, Nawaf Hussein; Alsaffar, Hussain Fuad; Hamza, Aseel Abubakr; Alaqlan, Mohammed Abdulrahman; Takrooni, Walaa Abdullah; Mandora, Ruba Mohammad; Althabi, Nabeel Ali; Alzekrey, Meshari Khaled; Khan, Hatan Adnan; et al. (International Journal Of Community Medicine And Public Health, 2021)
Although medications have shown great efficacies in managing generalized anxiety disorder (GAD), recent evidence shows that patients tend to psychotherapy as their first-line of management due to the frequency of side effects resulting from the prolonged use of these medications. Psychotherapy is defined as the using certain and defined psychological modalities for the management of an emotional or mental illness on the condition that the aim and deadline of the therapy have been pre-determined. In this review, we present a brief about the psychological management of patients with GAD. We have identified three psychological modalities for the management of GAD as previous studies have compared them to the usual care by pharmacological modalities or a placebo. These include cognitive-behavioral (CBT), interpersonal, and supportive therapies. We found that management of GAD using CBT, interpersonal or supportive therapies is significantly efficacious in reducing GAD symptoms and increase the possibilities of recovery in addition to reducing the recovery or relapse rates. By doing this, we expect that the managed patient’s quality of life would be improved. We also recommend that the management approach should be case-sensitive for each patient depending on the patient’s status, the severity of the disease, and the responsiveness of the patient.